2011
DOI: 10.1007/s10103-011-0969-z
|View full text |Cite
|
Sign up to set email alerts
|

Histological in vitro evaluation of the effects of Er:YAG laser on oral soft tissues

Abstract: In oral pathology, laser devices can provide important advantages, especially in the treatment of certain lesions. However, there is controversy about the use of some wavelengths in the analysis of suspected dysplastic or neoplastic lesions, raising doubt about the laser's suitability for use in biopsy procedures. In recent studies, the KTP and diode lasers have been used in biopsy procedures without histological artefacts. The aim of this in vitro study was to evaluate the exact extent of peripheral thermal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 15 publications
2
29
0
1
Order By: Relevance
“…Due to the important role of the biopsy, as the specimen taken is uniquely and thus not repeatable, even from a medical-legal point of view, this procedure needs to be performed within the full safety margins [14,15]. Since laser has been used in a versatile way as a useful device in the surgical field, even for biopsies, there have been several studies aimed to test its safety [10,18,20]; but there are several authors who, especially in the past, valued controversies in the use of these devices in the field of biopsy surgery [14,15,24]. The critical aspect is not the difficult diagnosis of the specimen, since the various laser devices are now able to guarantee a histological diagnosis, if used with the right parameters and by a skilled operator, but the legibility of the peri-incisional margins of the specimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the important role of the biopsy, as the specimen taken is uniquely and thus not repeatable, even from a medical-legal point of view, this procedure needs to be performed within the full safety margins [14,15]. Since laser has been used in a versatile way as a useful device in the surgical field, even for biopsies, there have been several studies aimed to test its safety [10,18,20]; but there are several authors who, especially in the past, valued controversies in the use of these devices in the field of biopsy surgery [14,15,24]. The critical aspect is not the difficult diagnosis of the specimen, since the various laser devices are now able to guarantee a histological diagnosis, if used with the right parameters and by a skilled operator, but the legibility of the peri-incisional margins of the specimen.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been made about the thermal effect on soft tissues of the oral cavity, both "ex vivo" and "in vivo", with CO 2 [6,16], diode [17], KTP [18], Nd:YAG [19] and Er:YAG [20] laser devices.…”
Section: Introductionmentioning
confidence: 99%
“…Another study carried out by Romeo et al [14] about the histological evaluation of Er:YAG laser effect on oral soft tissues showed that, using this device with intermediate power (80–100 mJ), the thermal damage was always under the millimeter involving only the epithelium layer. So, authors concluded that thermal damages was negligible and the readability of the perioincisional margins was always possible.…”
Section: Discussionmentioning
confidence: 99%
“…Esta absorción produce interacciones fotoquímicas, fototérmicas y fotomecánicas en los tejidos. En las mucosas se ha demostrado que el láser no ablativo Er:YAG estimula la producción de proteínas de matriz y fibroblastos, generando contracción de las fibras de colágeno y cambios tróficos que se manifiestan en tejidos con mayor grosor, hidratación y tensión (24)(25)(26)(27)(28).…”
Section: Discussionunclassified